Based on Atmospheric Physics and Ecological Principle to Assess the Accuracies of Field CO2/H2O Measurements From Infrared Gas Analyzers in Closed‐Path Eddy‐Covariance Systems. Issue 10 (21st October 2021) - Zhou, Xinhua; Gao, Tian; Pang, Yunchao; Mahan, Hayden; Li, Xiufen; Zheng, Ning; Suyker, Andrew E.; Awada, Tala; Zhu, Jiaojun
Abstract: Field CO2 /H2 O measurements from infrared gas analyzers in closed‐path eddy‐covariance systems have wide applications in earth sciences. Knowledge about exactness of these measurements is required to assess measurement applicability. Although the analyzers are specified with uncertainty components (zero drift, gain drift, cross‐sensitivities, and precision), exactness for individual measurements is unavailable due to an absence of methodology to comprehend the components as an overall uncertainty. Adopting an advanced definition of accuracy as a range of all measurement uncertainty sources, the specified components are composited into a model formulated for studying analyzers' CO2 /H2 O accuracy equations. Based on atmospheric physics and environmental parameters, the analyzers are evaluated using the equations for CO2 accuracy (±0.78 µmolCO2  mol −1, relatively ±0.18%) and H2 O accuracy (±0.15 mmolH2 O mol −1 ). Evaluation shows that precision and cross‐sensitivity are minor uncertainties while zero and gain drifts are major uncertainties. Both drifts need adjusting through zero/span procedures during field maintenance. The equations provide rationales to guide and assess the procedures. H2 O span needs more attentions under humid conditions. Under freezing conditions while H2 O span is impractical, this span is fortunately unnecessary. Under the same conditions, H2 O zero drift dominates H2 O measurement uncertainty. Therefore, automatic zero becomes a more applicable and necessary tactic. In general cases of atmospheric CO2 background, automatic CO2 zero/span procedures can narrow CO2 accuracy by 36% (±0.74 to ± 0.47 µmolCO2 mol −1 ). Automatic/manual H2 O zero/span procedures can narrow H2 O accuracy by 27% (±0.15 to ±0.11 mmolH2 O mol −1 ). While ensuring system specifications, the procedures guided by equations improve measurement accuracies. Key Points: Paper develops accuracy equations for CO2 /H2 O measurements from infrared gas analyzers in closed‐path eddy‐covariance systems The equations are used to assess the improvement in CO2 /H2 O measurement accuracy of analyzers under automatic zero/span procedures Assessments find that, for analyzers in cold/dry conditions, the zero procedure is important, but the H2 O span procedure is unnecessary